“A Desert Cactus”: The Literary Friendship of Katherine Anne Porter and Kay Boyle - Beth ALVAREZ (E-REA)
The literary friendship of Kay Boyle and Katherine Anne Porter is documented in Porter’s papers at the University of Maryland Libraries. The record includes fifty-seven letters exchanged between May 8, 1931, and July 1, 1976. An examination of this correspondence reveals mutual admiration, affection, and professional and personal respect.